Induction of Penicillinase with Inorganic Phosphate - Imsande, John (1967)
Phosphate stimulates penicillinase formation in Bacillus cereus 569. The rate of penicillinase synthesis in the presence of 0.3 m phosphate, pH 7.0, is approximately 10-fold greater than that for uninduced cells, while the rate of synthesis in the presence of 0.3 m phosphate and 1 unit/ml of penicillin is approximately fourfold greater than in the presence of penicillin alone. When phosphate-induced cells are transferred to low phosphate medium, the rate of penicillinase synthesis rapidly reverts to that of uninduced cells. Furthermore, the phosphate-induced synthesis of the enzyme is inhibited by either chloramphenicol or actinomycin D. These antibiotics are known to inhibit protein synthesis and deoxyribonucleic acid-dependent ribonucleic acid (RNA) synthesis, respectively. Thus, phosphate appears to induce the synthesis of a species of RNA that is required for the synthesis of penicillinase in B. cereus 569. The penicillin-dependent induction lag for penicillinase was compared in high and low phosphate media. It was found that, at 37 C, the penicillin-dependent lag is approximately 3 min in the presence of 0.3 m phosphate and approximately 6 min in low phosphate medium.